Covid-19 among the Brazilian Amazon indigenous people: factors associated with death - Cunha, Arthur Arantes da; Nazima, Maira Tiyomi Sacata Tongu; Castilho-Martins, Emerson Augusto (Saúde e Sociedade, 2022)
This case-control study paired by gender and age analyzes factors associated with the death of indigenous people from COVID-19 in the state of Amapá, Brazil. Data were collected from a public secondary database produced by the Amapá State Department of Health. Cases (n=29) were deaths of indigenous people from COVID-19 and controls were cures of the disease (n=87), recorded between April 2020 and January 2021. Data from individuals with active disease were excluded. Univariate analysis followed by multiple logistic regression were performed to study the independent variables associated with death. Most cases of death were women (51.7%), without comorbidities (62.1%), residing in cities of the Metropolitan Region of Macapá (RMM) (65.5%) and in urban areas (89.7%). Median age of the death group was 72 years (interquartile range=21.5). The final multiple model showed that indigenous individuals with cardiovascular comorbidity had a 4.01 times greater chance (95% confidence interval – 95% CI=1.05-15.36) of death by COVID-19 when compared with indigenous people without comorbidities. And that indigenous people residing in the RMM had a 2.90 times greater chance (95%CI = 1.10-7.67) of death when compared with indigenous residing in the countryside.